Pengaruh Ekstrak Buah Mengkudu (Morinda citrifolia) terhadap Waktu Kematian Cacing Ascaris suum, Goeze In Vitro - Riza Deviana; Cr. Siti Utari; Brian Wasita (Nexus Biomedika, 2012)
Background: Mengkudu (Morinda citrifolia) has a terapeutic effect, such as antibacterial, anthelmintic and imunomodulator. This research was performed to understand the effect of Mengkudu (Morinda citrifolia) fruit extract on death time of Ascaris suum, Goeze In Vitro. Methods: This research was performed using experimental laboratory method with post-test only controlled group design. Adult Ascaris suum, Goeze (108 worms) were divided into 9 groups. The worms treated with NaCl 0.9 % solution and Piperazine 0.4% g/ml served as negative control and positive control group consecutively. The worms treated with increasing dose of Mengkudu fruits (Morinda citrifolia) extract (1% g/ml, 2% g/ml, 4% g/ml, 6% g/ml, 8% g/ml, 10% g/ml, and 12% g/ml) served as treatment groups. Observations were performed every half hour until the worms died. LC50 and LT50 were calculated using probit analysis. Statistic analysis was performed using Kruskal-Wallis test continued by Post hoc Test with Bonferroni correction. Results: Probit analysis showed that LC50 and LT50 of Mengkudu fruits extract were 4.94% g/ml and 703.32 minutes. Kruskall-Wallis test showed that significance difference at least in the two groups. Post Hoc Mann-Whitney with Bonferroni correction test showed that treatment had significant difference (p < 0.001) to negative control and 12% g/ml group had significant difference to positive control group. Conclusions: Mengkudu (Morinda citrifolia) fruits extract can induce Ascaris suum death with the death time faster than standard medicine. Keywords: Mengkudu (Morinda citrifolia) extract, Ascaris suum, Piperazin.